Peningkatan Performa UMKM Melalui Strategi Pemasaran Digital Dalam Meningkatkan Penjualan (STMIK Dharmapala Riau, 2025)
This study aims to identify effective digital marketing strategies for culinary products and demonstrate how digital marketing can enhance the performance of small and medium-sized enterprises (SMEs). The approach used is qualitative, involving the collection of primary data through observations and interviews with relevant stakeholders. Secondary data has been gathered from books, journal articles, and other literature sources. The findings of this research reveal several significant insights. Firstly, SME owners believe that performance can be improved by creating engaging and memorable content that captures consumer attention. Secondly, from the consumers' vantage point, digital marketing enables SMEs to lower their costs and become more competitive compared to those that do not employ such strategies. Thirdly, the general public feels that SMEs need to enhance their digital marketing efforts to better present their product and company identities in today’s digital landscape. Overall, this research highlights the vital role of digital marketing for SMEs, especially in solidifying their market position. By implementing the right strategies, SMEs can not only boost their business performance but also broaden their market reach. This indicates that leveraging digital technology in marketing is a crucial step toward achieving success in the contemporary digital age. The secondary data utilized by the author was sourced from various books, journal articles, and supporting literature. Meanwhile, the findings from this research indicate that, firstly, SME owners consider that performance improvements can be attained solely by generating appealing and memorable content. Secondly, from the perspective of SME consumers, digital marketing can lower expenses and make them more competitive in comparison to those who do not utilize digital marketing. Lastly, based on public opinion.